MARKET SEGMENTATION BASED ON COMMUNITY INVOLVEMENT AT THE NURUL JADID ISLAMIC BOARDING SCHOOL - Fachri, Moh; Hefniy, Hefniy; Qodriyah, Khodijatul; Yakini, Lailatul (Managere: Indonesian Journal of Educational Management, 2022)
This study analyzes the market segmentation in the Nurul Jadid Islamic Boarding School Paiton Probolinggo. The method used is a case study qualitative approach. The data collection technique is done through interviews and document observation. The data analysis technique is carried out circularly, from data collection, reduction, display, and conclusions. The results of this study indicate that market segmentation based on community involvement is carried out by analyzing market segmentation, determining the target market, and creating a positive image. This research has implications for the importance of community involvement in building the quality of education at the Nurul Jadid Islamic Boarding School Paiton Probolinggo.